Copper toxicity compromises root acquisition of nitrate in the high affinity range - Feil, Sebastian B.; Zuluaga, Monica Yorlady Alzate; Cesco, Stefano; Pii, Youry (Frontiers in Plant Science, 2023)
The application of copper (Cu)-based fungicides for crop protection plans has led to a considerable accumulation of Cu in soils, especially in vineyards ones. Copper is indeed an essential micronutrient for plants, but relatively high concentrations in the growth substrate may cause toxicity phenomena, as for instance alteration of the plant growth and disturbance in the acquisition of mineral nutrients. This last aspect might be particularly relevant in the case of nitrate (NO3-), whose acquisition in plants is finely regulated through the transcriptional regulation of NO3- transporters and plasma membrane H+-ATPase in response to the available concentration of the nutrient. In the present study, cucumber plants were grown hydroponically and exposed to increasing concentrations of Cu (i.e., 0.2, 5, 20, 30 and 50 µM) to investigate their ability to respond to and to acquire NO3-. To this aim, the kinetic of substrate uptake and the transcriptional modulation of the molecular entities involved in the process have been assessed. Results showed that the inducibility of high affinity transport system was significantly affected by increasing Cu concentrations; at Cu levels higher than 20 µM, plants demonstrated either a strongly reduced or abolished NO3- uptake activity. Nevertheless, the transcriptional modulation of both the nitrate transporter CsNRT2.1 and the accessory protein CsNRT3.1 was not coherent with the hindered NO3- uptake activity. On the contrary, CsHA2 were downregulated, thus suggesting that a possible impairment in the generation of the proton gradient across the root PM could be the cause for the abolishment of NO3- uptake.